PENERAPAN METODE SOSIODRAMA DALAM PROMOSI KESEHATAN TENTANG PENULARAN HIV/AIDS PADA IBU RUMAH TANGGA - ulfah agus sukrillah (Kesmas Indonesia, 2018)
Research backgroud: Kinds of methodsin health promotion to address the spread and transmission of HIV/AIDS has been applied to the society. The focus of today's HIV-AIDS is housewifes. Method of sociodrama about the transmission of HIV/AIDS aims to provide an understanding, appreciation and develop their ability to solve the problem of HIV/AIDS through role play. The purpose ofthis research: is to determine the effect sociodrama in health promotion methods about transmission of HIV/AIDS towards housewives. Research method: The methodused is quasie xperimental with pre and post-test with control group design, where it measures the difference between before and after intervention using control groups. The differences between before and after the intervention are assumed to bethe effect of the intervention. The result of reserach: based on paired t test and independent t test both intervention group and control group before and after the treatment has p value (0,000) < α (0,05). It means that there was significant different in term of knowledge level between two groups. Conclusion : there is significant difference between sociodrama method with the use of audio- visual media in the delivery of health promotion about the transmission of HIV / AIDS on housewife.